Solvent-free and time-efficient Suzuki–Miyaura reaction in a ball mill: the solid reagent system KF–Al2O3 under inspection - Bernhardt, Franziska; Trotzki, Ronald; Szuppa, Tony; Stolle, Achim; Ondruschka, Bernd (Beilstein Journal of Organic Chemistry, 2010)
Although a plethora of synthetic procedures mediated by KF-loaded aluminas is available in the literature, there is almost no data concerning the influence of parameters such as alumina modification or KF-loading on experimental results. Hence, the Pd-catalyzed, solvent-free Suzuki–Miyaura reaction was chosen as model reaction to investigate the effect of the above mentioned parameters on the results of coupling reactions. The results from ball milling experiments led to the conclusion that self-prepared and commercially available KF–Al2O3 differ in water content. The higher the residual water content, the higher are the product yields.
Keywords: ball milling; C–C coupling; KF–Al2O3; palladium; solid reagent system